Wireless power transfer from unmanned aerial vehicle to low-power wide area network nodes: Performance and business prospects for LoRaWAN. (November 2019) - Tiurlikova, Aleksandra; Stepanov, Nikita; Mikhaylov, Konstantin
Supported by the remarkable progress across many technological domains, the Internet of Things (IoT) ecosystem demonstrates steady growth over the few past years. This growth enables a number of new exciting applications. Nonetheless, hardly one can say today that the utility of the IoT is used to its full potential. This fact is especially notable for the monitoring applications deployed in remote areas. To address the needs of these use cases, in the article we propose a solution based on the combination of three key technologies: the low-power wide area networks, the unmanned aerial vehicles, and the wireless power transfer. In the article, we first detail the novel concept of a wireless power transfer-enabled unmanned aerial vehicle employed to charge the LoRaWAN sensor nodes. Then, via extensive simulations and analysis of an illustrative LoRaWAN application, we investigate both technical and, notably, business performance indicators, and compare them against the ones for a baseline scenario with no unmanned aerial vehicle. Our results illustratively demonstrate that in the long-term perspective, the inclusion of a wireless power transfer-enabled drone may drastically reduce the system's operating expenses. At the very same time, our results highlight the limits, bottlenecks, and trade-offs related to the proposed concept, thus providing the basis and calling for further investigation.